MEMBELAJARKAN MATERI PENYEMBELIHAN DENGAN METODE MODELING DAN ALAT PERAGA DI SMP NEGERI 27 PURWOREJO - Eko Nuswantoro (Asaatidzah, 2022)
Slaughter material often experiences problems being taught in class because it is relatively complex to be taught in real terms. The costs that must be incurred to buy animals for slaughter and the risks that must be faced when the slaughter is illegal. On the other hand, the competency in slaughtering animals is demanded by the curriculum. The purpose of this study was to find out the scenarios of applying the modeling method with props to slaughtering material for students and the strategy for applying the modeling method to teaching aids to slaughtering, aqiqah and qurban material. Recovery of learning through Classroom Action Research which is carried out through 2 cycles, each cycle consisting of planning, action, observation and reflection stages. Methods of data collection obtained by means of performance tests, and observation techniques. Furthermore, the data were analyzed using descriptive quantitative statistics. This study shows that: 1) The modeling method with teaching aids can be applied to slaughtering material with the teacher's technique as a model and the selected student's technique as a model; 2) The application of the modeling method with teaching aids can increase students' understanding by increasing the average test results performance to 80.31.